Probiotics in the Management of Antibiotic-Associated Diarrhea in Children: A Systematic Review and Meta-analysis of Randomized and Controlled Trials - Fadin, Larissa; Vieira, Karolinny Cristiny De Oliveira; Toledo, Ana Clara Campagnolo Gonçalves; Da Silva, Anne Kastelianne França [UNESP]; Pereira, Valéria Cataneli; Winkelstroter, Lizziane Kretli (Wolters Kluwer, 2023)
This review aimed to evaluate probiotic use to prevent antibiotic-associated diarrhea in children. A total of 1564 studies of randomized clinical trials published in English were found using PubMed, Cochrane, and Virtual Health Library (MEDLINE/LILACS). A meta-analysis included 4 trials in subgroup Lactobacillus rhamnosus (95% confidence interval [CI]: 0.17-0.49; P <.00001), 2 trials in subgroup L reuteri (95% CI: 0.51-1.77; P =.87), and 5 groups in subgroup association of species of probiotics (95% CI: 0.21-1.71; P =.33). The findings suggest that L rhamnosus alone may be useful in preventing antibiotic-associated diarrhea in children.
Keywords: gastrointestinal microbiome; Lactobacillus; probiotics